2020
DOI: 10.7150/thno.36722
|View full text |Cite
|
Sign up to set email alerts
|

Coniferaldehyde attenuates Alzheimer's pathology via activation of Nrf2 and its targets

Abstract: Background: Alzheimer's disease (AD) currently lacks a cure. Because substantial neuronal damage usually occurs before AD is advanced enough for diagnosis, the best hope for disease-modifying AD therapies likely relies on early intervention or even prevention, and targeting multiple pathways implicated in early AD pathogenesis rather than focusing exclusively on excessive production of β-amyloid (Aβ) species.Methods: Coniferaldehyde (CFA), a food flavoring and agonist of NF-E2-related factor 2 (Nrf2), was sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 85 publications
1
40
0
Order By: Relevance
“…Dong et al. (2020) reported that the phosphorylation of GSK3β was considerably higher in cells treated with CA (10 and 100 µM). Therefore, it was speculated that CA treatment enhanced intracellular glycogen content by increasing the phosphorylation of GSK3β and decreasing the phosphorylation of GS in PA‐induced HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dong et al. (2020) reported that the phosphorylation of GSK3β was considerably higher in cells treated with CA (10 and 100 µM). Therefore, it was speculated that CA treatment enhanced intracellular glycogen content by increasing the phosphorylation of GSK3β and decreasing the phosphorylation of GS in PA‐induced HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…CA is a derivative of cinnamaldehyde, which is a natural flavorant and improves liver steatosis and insulin resistance in diabetic rats (Dong et al., 2020; Zhu et al., 2017). A previous study showed that the bioavailability of cinnamaldehyde was approximately 20% after oral administration in rats (Zhao et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mouse model of Alzheimer’s disease, coniferaldehyde, an active ingredient in propolis, had neuroprotective effects. It reduced brain β-amyloid deposits and pathological changes in the brain, helping preserve learning and memory capacity [ 156 ]. The angiotensin system, which is key to SARS-CoV-2 invasion of host cells, is associated with senescence.…”
Section: Comorbidities and Evidence Of How Propolis Can Help Reduce Tmentioning
confidence: 99%